Pengetahuan Remaja Tentang Pendewasaan Usia Perkawinan Dengan Niat Untuk Menikah Pada Usia Muda - Anita Puji Lestari; Nining Tunggal Sri Sunarti; Kurniasari Pratiwi (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2014)
Background: Marriage at a young age have an impact on improving maternal mortality, unwanted pregnancy, abortion, the number of abandoned children, unemployment and divorce. In an effort to overcome these problems the government makes a family planning program aimed suppress the population growth rate is one of the maturation age of marriage.Objective: To determine the relationship of adolescent knowledge about the maturation age of marriage with the intention to marry at a young age in Junior High School Muhammadiyah PiyunganMethods: This research used quantitative methods with cross sectional approach. The population in this study is the eighth grade students of junior high school Muhammadiyah Piyungan 2013-2014 school year as many as 71 students. Sampling with a total sampling technique.Results: Adolescents who have a good knowledge of the maturation age of marriage 28 (39.4%) of respondents, knowledgeable enough 35 (49.3%) of respondents. Teenagers who do not intend to get married very young 33 (46.5%) of respondents, had no intention of 37 (52.1%) of respondents. The results of statistical tests using Kendal Tau (τ) obtained a significance of 0.017.Conclusion: There is a relationship between adolescent knowledge about the maturation age of marriage with the intention of getting married at a young age.Keywords: Maturation age of marriage, Marriage young age